Estimation of patient dose in computed tomography: an extension of IAEA Project in Brazil - Delduck, Romulo S.; Kodludovich, Simone; Oliveira, Larissa C.; Silveira, Vinícius C.; Silva, Humberto O.; Khoury, Helen; Nader, Alejandro (Revista Brasileira de Física Médica, 2015)
The aim of this paper was to estimate the patient’s dose in routine procedures in Brazil and to identify the potential of optimization in adults and pediatric procedures. The sample included ten hospitals distributed in different states of the country. In each hospital, the routine protocols of head, chest, high resolution chest, abdomen, and pelvis were recorded. The values of Cw , Cvol and Pkl were estimated based on the n Cw values provided by IMPACT. For the same procedure, significant differences in patient’s doses were verified between the hospitals and also in the same department. In some cases, the technical factors are so low that suggest a rigorous evaluation of the image quality. Problems were also observed regarding procedures records, and the information about the procedure is insufficient. This study indicated the necessity of an implementation of an action plan that includes training program to operate the scanner in an optimized mode, to carry out the dosimetry, and to evaluate the image quality. The large range of patient’s doses indicated that there is an expressive potential of patient’s dose reduction and optimization maintaining the diagnostic information.